Trias Politica di Indonesia : Kajian Perbandingan dengan Konsep Fiqih Siyasah - Roidatus Shofiyah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study aims to analyze the application of the Separation of Powers concept in the Indonesian political system and compare it with the concept of Fiqh Siyasah in Islam. The Separation of Powers theory was first introduced by the French philosopher Montesquieu in the 18th century, dividing state authority into three main branches: legislative, executive, and judicial. This research examines how this concept is applied in the Indonesian political system and compares it with the distribution of power in Fiqh Siyasah, which also divides state power into three branches: executive, legislative, and judicial. The study further explores the relationship between these two concepts by examining the practices of governmental powers in Indonesia and their connection to the principles of Fiqh Siyasah. The findings indicate that there is a convergence in some aspects of the application of Separation of Powers in Indonesia with Fiqh Siyasah in Islam, but challenges in implementation require further development to achieve an effective balance between state institutions.